(untitled) (Mutah Journal of Humanities and Social Sciences (MJHSS), 2024)
The study aimed to determine the extent to which some physical measurements and kinematic variables contribute to the results of the horizontal and vertical jumps from stability tests. b hnbh ygbn c6ytgby6tgbttThe researchers used the descriptive approach in which corelationships were examined, and the study was run on a purposive sample of (42) male students from the Faculty of Physical Education at Yarmouk University who were enrolling in the practical courses, where physical measurements were taken of them, and then they were photographed while performing the horizontal and vertical jump tests from stability using a camera from of Canon type, which takes up to 30 images a second. The researchers extracted the kinematic variables using the Kenova software, and the data was entered into the computer and processed with the statistical analysis program for the social sciences (SPSS) in order to calculate the means, standard deviations, skewness coefficients, correlation coefficients, and multiple linear regression analysis . The results showed no statistical contribution to anthropometrics on the horizontal or vertical jump, while there was a statistical contribution on the vertical or horizontal jump of the kinematic variables, for both time and speed of the jump. The researchers recommended that researchers should focus on studying the kinematic variables as they relate and contribute to the distance of the horizontal and vertical jump from stability.